2013
DOI: 10.1186/1471-2474-14-364
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of continuous – wave microwave irradiation did not cause temperature increase in muscles tissue adjacent to titanium alloy implants – an animal study

Abstract: BackgroundResearch studies on the influence of radiofrequency electromagnetic radiation on implants in vitro have failed to investigate temperature changes in the tissues adjacent to the implants under microwave therapy. We therefore, used a rabbit model in an effort to determine the impact of microwave therapy on temperature changes in tissues adjacent to the titanium alloy implants and the safety profile thereof.MethodsTitanium alloy internal fixation plates were implanted in New Zealand rabbits in the middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The unique properties of titanium alloy provide an opportunity to investigate the effects of microwaves. Ye et al ( 27 , 28 ) demonstrated that 25 W microwave (2,450 MHz) promoted fracture rehabilitation in an animal model with a titanium alloy implant with no dramatic increase in heat (<41°C). To the best of our knowledge, the effect of microwaves on the skeletal muscles adjacent to fracture sites has not yet been investigated, hindering the application of this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique properties of titanium alloy provide an opportunity to investigate the effects of microwaves. Ye et al ( 27 , 28 ) demonstrated that 25 W microwave (2,450 MHz) promoted fracture rehabilitation in an animal model with a titanium alloy implant with no dramatic increase in heat (<41°C). To the best of our knowledge, the effect of microwaves on the skeletal muscles adjacent to fracture sites has not yet been investigated, hindering the application of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the magnetic permeability and electric conductivity of titanium alloy is lower than conventional biomedical metal implants ( 25 , 26 ). Ye et al ( 27 ) performed two randomized controlled studies and demonstrated that 25 W microwave (2,450 MHz) improved the healing of fractures with titanium alloy internal fixation without irreversible heat damage (<41°C) in a rabbit model. Ye et al ( 28 ) also reported that the temperature of muscle tissue adjacent to titanium alloy implants is beyond the scope of security (>41°C) when the power of microwave irradiation is tuned to 50 W. This report alone is insufficient and further research is required to reach a new consensus.…”
Section: Introductionmentioning
confidence: 99%
“…The following experiments verify this hypothesis. In vivo animal studies by Ye et al [ 23 , 24 ] showed that there was no obvious histological change in the skeletal muscles and nerves near the titanium alloy implant when single irradiation with 2450 MHz microwave at a lower dose (20 W~40 W) or continuous irradiation with 25 W titanium alloy fixed rabbit femoral fracture. However, with the increase of power (60 W and 80 W), acute thermal injury of skeletal muscle and nerve could be observed.…”
Section: Introductionmentioning
confidence: 99%